Shape Stability of Polyethylene Glycol/Acetylene Black Phase Change Composites for Latent Heat Storage. (24th October 2018) - Zhang, Jingjing; Li, Hairong; Tu, Junyang; Shi, Ruonan; Luo, Zhiping; Xiong, Chuanxi; Jiang, Ming
Abstract : Sufficient shape stability is essential for a high-performance phase change material (PCM). Although significant advances have been made to develop form-stable composites, technical development in the field of polymer-based PCMs is currently limited by an incomplete understanding of the shape stability. Form-stable polyethylene glycol/acetylene black (PEG/AB) PCMs containing PEGs with different average molecular weights have been obtained by melt mixing to investigate the shape stability of the PEG/AB composites. It was found that the phase change behaviors of the PEG/AB composites were not only attributed to the interactions between the AB and PEG, but also to the intermolecular interactions of the PEG chains, depending on the varying molecular weights of the PEGs. Physically crosslinked structure with temporary junctions was formed through hydrogen bonding, capillary, surface tension forces, intermolecular friction, and macromolecular entanglement, which contributed to the constrained chain motion and thus the solid-solid phase change behavior of the PEG/AB composites. The physically crosslinked structure was more stable with longer length of the PEG molecular chains, resulting in higher critical impregnated contents of the PEG into the AB and thus improved latent heat.